Open work between rational aesthetics and symbol : indagini di filosofia dell’arte a partire da Magritte - Quargnolo, Massimo (Scenari, 2021)
This paper investigates potential occurrences of classical instances concerning philosophy of art or aesthetics in the traditional sense (i.e. around beauty, performance, the nature of a piece of artwork, symbolism, and art criticism) in pictorial figurative art, not within a hermeneutic theoretical context (typical to postmodern philosophy, where the interpreter’s role is absolute). Rather, this investigation uses ideas that are commonly found in rational aesthetics and in experimental phenomenology, in the context of philosophical realism. This paper will study the impact of how visual perception is able to unify, and the subsequent cognitive disruption it creates (referencing particularly Rene Magritte’s artistic output), in light of its poetic and aesthetic potential. It is an experiment of immersion into a theoretical realist universe, relating to the “open work” concept pioneered by Umberto Eco, and also a critical examination of the often mysterious titles of Magritte’s paintings. Lastly, the paper’s analysis of such “perceptual games” will be connected to the appropriate historical and cultural context, drawing ontological conclusions from the symbolism they provide, including across moments in the history of the Arts from different countries and eras.